2008
DOI: 10.1038/onc.2008.378
|View full text |Cite
|
Sign up to set email alerts
|

The myxoid liposarcoma FUS-DDIT3 fusion oncoprotein deregulates NF-κB target genes by interaction with NFKBIZ

Abstract: FUS (also called TLS), EWSR1 and TAF15 (also called TAF2N) are related genes involved in tumor type-specific fusion oncogenes in human malignancies. The FUS-DDIT3 fusion oncogene results from a t(12;16)(q13;p11) chromosome translocation and has a causative role in the initiation of myxoid/round cell liposarcomas (MLS/ RCLS). The FUS-DDIT3 protein induces increased expression of the CAAT/enhancer-binding protein (C/EBP) and nuclear factor-jB (NF-jB)-controlled gene IL8, and the N-terminal FUS part is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 48 publications
4
67
0
2
Order By: Relevance
“…The C-terminus of FUS co-activates p65 and plays a pivotal role in NF-kappaB mediated transcription though this C-terminus is lost in the FUS/DDIT3 fusion protein. Recent studies showed that the FUS/DDIT3 fusion protein facilitates NF-kappaB binding to its target genes, probably in an indirect manner[19,39-41]. The FUS-DDIT3 fusion protein deregulates NF-kappaB controlled genes by interaction with nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor zeta (NFKBIZ)[19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminus of FUS co-activates p65 and plays a pivotal role in NF-kappaB mediated transcription though this C-terminus is lost in the FUS/DDIT3 fusion protein. Recent studies showed that the FUS/DDIT3 fusion protein facilitates NF-kappaB binding to its target genes, probably in an indirect manner[19,39-41]. The FUS-DDIT3 fusion protein deregulates NF-kappaB controlled genes by interaction with nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor zeta (NFKBIZ)[19].…”
Section: Discussionmentioning
confidence: 99%
“…Data on activated pathways in myxoid liposarcoma are sparse[18,19]. By using a kinase substrate specific protein array chip combining 1024 different kinase substrates, we identified kinases associated with Src and NF-kappaB pathways to be active in myxoid liposarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…At the genetic level, the most characteristic change is a t(12;16) (q13;p11) chromosomal translocation that results in the fusion of the FUS and DDIT3 genes (16,17). The cellular origin of these tumors is unknown, but preadipocytic progenitor cells and mesenchymal stem cells have been implicated (18); after embryogenesis, the mitotic activity of these cells is thought to be low.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent translocations have typically been interpreted as important for tumorigenesis, and, for example, the FUS-DDIT3 gene fusion has been described as oncogenic in liposarcoma. 189 However, there is growing evidence that recurrent translocations can also be passenger events in cancer. 190 In conclusion, there is increasing evidence of the extent and importance of aberrant splicing in cancer.…”
Section: Dysregulation Of Splicing In Cancermentioning
confidence: 99%